Impacts of habitat fragmentation on the genetic diversity of the endangered Guatemalan fir (Abies guatemalensis Rehder) - Ruiz-Chután, José Alejandro; Kalousová, Marie; Lojka, Bohdan; Colocho-Hernández, Sofia; Prado-Córdova, José Pablo; Montes, Luis; Sánchez-Pérez, Amilcar; Berdúo-Sandoval, Julio Ernesto (Genetica, 2024)
Abies guatemalensis Rehder, an endangered conifer endemic to Central American highlands, is ecologically vital in upper montane forests. It faces threats from habitat fragmentation, unsustainable logging, and illegal Christmas tree harvesting. While previous genetic studies on mature trees from eighteen populations showed high within-population diversity and limited among-population differentiation, the genetic impact of recent anthropogenic pressures on younger generations has yet to be discovered. Understanding these effects is crucial for developing effective conservation strategies for this vulnerable species. We sampled 170 young trees (< 15 years old) from seven populations across Guatemala. Seven microsatellite markers were used to analyse genetic diversity, population structure, and recent demographic history. Moderate levels of genetic diversity were observed within populations (mean Shannon diversity index = 4.97, mean Simpson's index = 0.51, mean allelic richness = 11.59, mean observed heterozygosity = 0.59). Although genetic structure broadly aligned with mountain corridors, substantial admixture patterns suggest historical connectivity across all populations. Most populations showed evidence of recent bottlenecks (p < 0.05) and inbreeding. The results suggest a potential decline in genetic diversity and increased population structuring (ΦST = 0.274, p < 0.01) over the past decades compared to the previous study on old trees. The observed genetic patterns indicate ongoing impacts of habitat fragmentation and anthropogenic pressures on A. guatemalensis. Conservation efforts should prioritise expanding effective population sizes and facilitating gene flow, particularly for isolated populations. While restoration efforts may be logistically easier within mountain ranges, genetic evidence suggests that increasing overall population connectivity could benefit this species. Management strategies should implement systematic seed collection protocols to maintain genetic diversity in future populations. These findings highlight the urgent need for conservation measures to preserve remaining genetic diversity and promote connectivity among A. guatemalensis populations.
Keywords: Genetic bottleneck; populační genetika; Ecosystem; Conservation; genetická variace; Genetics, Population; mikrosatelitní repetice; Endangered Species; jedle; Gene flow; Overexploitation; Inbreeding; Abies; Microsatellite Repeats; Conservation of Natural Resources; Guatemala; zachování přírodních zdrojů; ekosystém; Genetic Variation; Guatemalan fir; ohrožené druhy